Social exclusion and health inequalities in the time of COVID-19 - Bejaković, Predrag; Škare, Marinko; Pržiklas Družeta, Romina (Technological and Economic Development of Economy, 2021)
Social exclusion as a process leads to a state of multiple relative deprivations in diverse areas of social life, like employment, education, healthcare, social ties, respect. Individuals or groups may have a worse position in several areas, particularly with other individuals or groups in society. Coronavirus pandemics disproportionately affect poorer communities and socially excluded people. Socially excluded are double victims; due to their position, they are more prone to infection by a coronavirus, further increasing their exclusion. The purpose of this contribution is to provide a conceptual framework for analyzing the relationship between social exclusion and health disparities during the COVID-19 pandemic. The goal is to comprehend the causes and consequences of unequal power relationships and offer critical assessments of current policies and measures to reduce health inequalities. Health and social inequalities are a significant constraint to economic revival and a successful fight against pandemics. The extent of the economic and health crisis caused by pandemic shock largely depends on past health and social inequality.